2021
DOI: 10.1101/2021.02.12.430998
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 mutations acquired in mink reduce antibody-mediated neutralization

Abstract: Transmission of SARS-CoV-2 from humans to farmed mink was observed in Europe and the US. In the infected animals viral variants arose that harbored mutations in the spike (S) protein, the target of neutralizing antibodies, and these variants were transmitted back to humans. This raised concerns that mink might become a constant source of human infection with SARS-CoV-2 variants associated with an increased threat to human health and resulted in mass culling of mink. Here, we report that mutations frequently fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 40 publications
3
37
0
Order By: Relevance
“…Here, we demonstrate that the L452R and Y453F mutations contribute to escape from HLA-restricted cellular immunity. In addition to our findings, recent papers have documented that the L452R (Deng et al, 2021;Li et al, 2020) and Y453F (Baum et al, 2020;Hoffmann et al, 2021b) substitutions may confer resistance to neutralizing antibodies, suggesting that these mutants can evade both humoral and HLA-restricted cellular immunity. Furthermore, we demonstrate that the L452R mutation significantly improves viral replication capacity by increasing binding affinity to human ACE2 as well as S protein stability.…”
Section: Discussionsupporting
confidence: 82%
“…Here, we demonstrate that the L452R and Y453F mutations contribute to escape from HLA-restricted cellular immunity. In addition to our findings, recent papers have documented that the L452R (Deng et al, 2021;Li et al, 2020) and Y453F (Baum et al, 2020;Hoffmann et al, 2021b) substitutions may confer resistance to neutralizing antibodies, suggesting that these mutants can evade both humoral and HLA-restricted cellular immunity. Furthermore, we demonstrate that the L452R mutation significantly improves viral replication capacity by increasing binding affinity to human ACE2 as well as S protein stability.…”
Section: Discussionsupporting
confidence: 82%
“…The second significant cluster with DH69/V70 and RBD mutants involves Y453F, another spike RBD mutation that increases binding affinity to ACE2 (Starr et al, 2020b), and has been found to be associated with mink-human infection (Munnink et al, 2021). Y453F has also been described as an escape mutation for mAb REGN10933, shows reduced susceptibility to convalescent sera (Baum et al, 2020;Hoffmann et al, 2021), and is possibly a T cell escape mutation (Motozono et al, 2021). DH69/V70 was first detected in the Y453F background on August 24, 2020 and so far appears to be limited to Danish sequences (Figures 1 and 5B), although an independent acquisition was recently reported along with DH69/V70 in an immunecompromised Russian individual with chronic infection (Bazykin et al, 2021).…”
Section: Dh69/v70 Spike Compensates For Reduced Infectivity Of Rbd Escape Mutantsmentioning
confidence: 99%
“…acknowledges funding by BMBF (01KI2006D, 01KI20328A, 01KI20396, 01KX2021), the Ministry for Science and Culture of Lower Saxony ( 14 Hannover, Germany), BHK-21 (Syrian hamster, male, kidney; ATCC Cat# CCL-10; RRID: CVCL_1915, kindly provided by Georg Herrler, University of Veterinary Medicine, Hannover, Germany) and Vero76 cells (African green monkey, female, kidney; CRL-1586, ATCC; RRID: CVCL_0574, kindly provided by Andrea Maisner, Institute of Virology, Philipps University Marburg, Marburg, Germany) were cultivated in Dulbecco's modified Eagle medium (DMEM) supplemented with 10% fetal bovine serum (FCS, Biochrom or GIBCO), 100 U/ml of penicillin and 0.1 mg/ml of streptomycin (PAN-Biotech). Caco-2 (human, male, intestine; HTB-37, ATCC, RRID:CVCL_0025), Calu-3 (human, male, lung; HTB-55, ATCC; RRID: CVCL_0609, kindly provided by Stephan Ludwig, Institute of Virology, University of M€ unster, Germany) and Calu-3 cells stably overexpressing ACE2, Calu-3 (ACE2) (Hoffmann et al, 2021c), were cultivated in minimum essential medium supplemented with 10% FCS, 100 U/ml of penicillin and 0.1 mg/ml of streptomycin (PAN-Biotech), 1x non-essential amino acid solution (from 100x stock, PAA) and 1 mM sodium pyruvate (Thermo Fisher Scientific). Calu-3 (ACE2) cells further received 0.5 mg/ml puromycin (Invivogen).…”
Section: Acknowledgmentsmentioning
confidence: 99%